PROJECT BASED LEARNING BERBASIS INTERNET OF THINGS UNTUK MENINGKATKAN KETERAMPILAN PROSES SAINS PESERTA DIDIK - Indarini Dwi Pursitasari; Didit Ardianto; Tita Dewi Larashati (Jurnal Penelitian Pendidikan IPA, 2023)
This study aims to analyze the application of Project Based Learning to improve science process skills (SPS) using IoT-based learning media. The method is qualitative and quantitative with a quasi-experimental type namely a pre-test-post-test control group. The population is students of class XII MIPA in one of the State Senior High Schools in Bogor City, totaling 214 students. Sampel for experimental and control classes were selected purposively, each with 35 students. Data were obtained through written tests, product assessments, observations, and questionnaires. Data analysis is included descriptive, validity test, reliability test, and t-tests. The results showed in the control, the SPS pre-test was not good and the post-test was good with a fairly large n-gain value. In the experimental class, the SPS pre-test was not good and the post-test was very good. The N-gain of the experimental class is higher than the control class. The SPS value of each indicator increased both in the control and experimental classes.Â  PjBL is able to improve SPS and the t-test shows the application of PjBL of PjBL with IoT on unidirectional electrical physics material